SYSTEM QUALITY, FEATURES, SERVICES, AND SYARIAH COMPLIANCE OF THE BYOND BY BSI APPLICATION: DETERMINING FACTORS OF INDONESIAN SYARIAH BANK CUSTOMER SATISFACTION IN THE ACADEMIC ENVIRONMENT - Salsabila Zahra Nasution (Universitas Islam Negeri Sumatera Utara, 2025)
This study was conducted to determine the determinants of customer satisfaction of Bank Syariah Indonesia at Medan State Polytechnic. The independent variables in this study include system quality, features, service quality and sharia compliance and the dependent variable is customer satisfaction. The sample in this study was 100 respondents, with stratified random sampling technique. Primary data was obtained from questionnaires distributed to Polmed academics who use BYOND by BSI. Data analysis techniques used multiple linear regression, Pearson correlation test, t test, F test, determination test and Classical Assumption test and data processing using SPSS 26. The results showed that the System Quality Variable partially had a strong and significant positive effect on customer satisfaction of Bank Syariah Indonesia at Medan State Polytechnic and the Service Quality Variable partially had a strong and significant positive effect on customer satisfaction of Bank Syariah Indonesia at Medan State Polytechnic while the Feature Variable partially had no significant effect on customer satisfaction of Bank Syariah Indonesia at Medan State Polytechnic and the Sharia Compliance Variable partially had no significant effect on customer satisfaction of Bank Syariah Indonesia at Medan State Polytechnic. The variables of System Quality, Features, Service Quality and Sharia Compliance of the BYOND by BSI Application simultaneously have a significant effect on customer satisfaction of Bank Syariah Indonesia at the Medan State Polytechnic.